The strategically located land index support system for human settlements land reform in South Africa. (February 2017) - Musakwa, Walter; Tshesane, Rebone.M.; Kangethe, Matheri
Abstract: Creating sustainable human settlements is fundamental in fostering spatial and socio-economic integration in South Africa. Policy makers are often faced with the problem of identifying strategically located land for human settlements land reform in South Africa. To date there is no tool or standard framework that assists the government to identify land that is strategically located for land reform. This study proposes the use of Geographic Information Systems (GIS), and Multi-Criteria Decision Making (MCDM) to develop a Strategically Located Land Index (SLLI) deployed in a web viewer to identify land that is smart for human settlements land reform. The study demonstrates that GIS, MCDM and the SLLI are invaluable tools in facilitating streamlined, coordinated, standardised and evidence-based decisions for human settlements land reform. However, there is need for capacity building in government departments responsible for land reform and development planning for the SLLI to be fully utilised. Highlights: We present a solution in identifying land suitable for settling people for land reform in South Africa. We utilize GIS and MCDA to assist decision makers in identifying areas suitable for smart human settlements. A collaborative and participatory GIS MCDA technique in identifying land suitable for human settlements is proposed.